HUBUNGAN TERAPI HEMODIALISA DENGAN PEMENUHAN ACTIVITY DAILY LIVING DI RSUD WALED KABUPATEN CIREBON - Amaliyah; Nonok Karlina; Citra Setyo Dwi Andhini (LPPM ITEKES Mahardika, 2019)
Patients with chronic kidney failure globally more than 500 million people. Every year it has increased. To overcome this kidney failure hemodialysis therapy is needed. However, patients undergoing hemodialysis will experience patient lifestyle problems, such as disruption of daily activities due to unstable body conditions and having to undergo routine processes. The purpose of this study was to identify the relationship of hemodialysis therapy with the fulfillment of Activity Daily Living (ADL) in Waled District Hospital Cirebon. This type of research is descriptive correlational with a retrospective approach. Sampling using a purposive sampling technique totaling 99 respondents. The instrument used was a questionnaire. Data analysis using the Spearman rank test. The research site was in the Waled District Hospital in Cirebon Regency during June 2019. The results showed that the duration of hemodialysis therapy carried out in the hemodialysis room at the Waled District Hospital in Cirebon District was in the chronic category of 71 respondents (71.7%) and the fulfillment of Activity Daily Living (ADL) in the category of severe functional impairment was 68 respondents (68.7%). Spearman rank test results (Pvalue ꞊ 0.027; ≤ 0.05; r꞊ 0.222). The direction of the correlation is positive, the longer the hemodialysis therapy is done, the severe functional disorder occurs. Nurses are expected to provide counseling to patients and families in identifying the ability of patients and families to meet the daily living activity (ADL).",